The relative risks of hyperglycaemia, obesity and dyslipidaemia in the relatives of patients with Type II diabetes mellitus. - Shaw, J; Purdie, D; Neil, H; Levy, J; Turner, R (1999)
Type II (non-insulin-dependent) diabetes mellitus has a substantial genetic component; however, its molecular basis remains largely unknown. The mode of inheritance is likely to be polygenic, with penetrance influenced by environmental factors. Although the familial aggregation of Type II diabetes is acknowledged, there is little data concerning the prevalence of diabetes in the relatives of subjects with diabetes in comparison with the general population, and our objective was to address this question in the defined geographic region of Oxfordshire, England. We studied 139 first degree relatives of 90 probands with Type II diabetes who attended routine diabetes clinics in Oxfordshire and documented the fasting plasma glucose, triglyceride and HDL-cholesterol concentrations and BMI of these subjects. The probands were selected without regard to family history of diabetes. The control population data were derived from two large-scale Oxford community studies which documented the prevalences of known and newly diagnosed diabetes. The prevalences of newly diagnosed and known diabetes were calculated for each group. The mean BMI, and concentrations of fasting glucose, triglyceride and HDL-cholesterol were compared and prevalence ratios for obesity (defined as BMI > 30 kg/m2), hyperglycaemia (defined as fasting plasma glucose > or = 6.1 mmol/l), and dyslipidaemia (defined as triglyceride > 2.0 mmol/l, HDL < 1.0 mmol/l) were calculated. There was a fourfold higher prevalence of hyperglycaemia in the first degree relatives of subjects with Type II diabetes compared with the control population: the prevalence ratio after adjustment for age, sex and BMI was 4.32 (95 % confidence interval 2.29-8.17). The relatives had a considerably higher fasting plasma glucose concentration than the control population (5.18+/-0.67 mmol/l (mean +/- 1 SD) vs 4.76+/-1.59 mmol/l, p = 0.0001), and this difference remained statistically significant after adjustment for age, sex and obesity. The relatives were significantly more obese, had higher fasting plasma insulin concentrations and had lower HDL-cholesterol concentrations. In conclusion, there is a strong familial aggregation of hyperglycaemia and obesity in the relatives of subjects with Type II diabetes and these subjects have higher fasting plasma insulin concentrations and lower HDL-cholesterol than the general population. These data indicate the particular relevance of screening the first degree relatives of subjects with Type II diabetes, as intervention strategies which aim to improve the metabolic profile are indicated for a large proportion of these subjects.